Tertib hukum pembentukan peraturan perundang-undangan pasca putusan Mahkamah Konstitusi - Haru Permadi (University of Merdeka Malang, 2020)
The state of law the main aspect that must be considered is legal certainty. Legal certainty can be realized with the government forming legislation that does not conflict between legal components. One component of the law is a judicial decisions which in this article focuses on the Constitutional Court’s decisions. One of the Constitutional Court’s decisions is the decision on the examination of the Act against the Constitution. In that decision there are statements that contradict or not contradict a norm that is tested by the Constitution. This research purpose is to examine whether the Constitutional Court’s decisions is considered by the legislators to realize legal certainty. A method of writing in this research uses the method of doctrinal research or commonly referred to as normative research. The research results show that there are legislations which are formed in opposition of the Constitutional Court’s decisions particularly relating to judge the legal opinion. Minister of Law and Human Rights Regulation No. 14 of 2019 concerning Ratification of Cooperatives mentions in Article 6 paragraph (3) there are five types of cooperatives, whereas the Constitutional Court's decisions mentions that restrictions on the type of cooperatives will block the creativity of cooperatives. Therefore the guarantee of legal certainty in the legislation does not materialize.How to cite item: Permadi, H. (2020). Tertib hukum pembentukan peraturan perundang-undangan pasca putusan Mahkamah Konstitusi. Jurnal Cakrawala Hukum, 11(1), 50-59. doi:https://doi.org/10.26905/idjch.v11i1.3642